Mineral Loss and Morphological Changes in Dental Enamel Induced by a 16% Carbamide Peroxide Bleaching Gel - Soares, Diana Gabriela; Ribeiro, Ana Paula Dias; Sacono, Nancy Tomoko; Loguercio, Alessandro Dourado; Hebling, Josimeri; Costa, Carlos Alberto De Souza (Fundação Odontológica de Ribeirão Preto, 2013)
The aim of this study was to compare the effect of a 16% carbamide peroxide (CP) gel and a 10% CP gel on mineralized enamel content and morphology. Enamel blocks from bovine incisors were subjected to a 14-day treatment (8 h/day) with 10% or 16% CP gels. Knoop microhardness was evaluated before bleaching and at 1, 7 or 14 days after this treatment (50 g/15 s). Mineral content (energy-dispersive x-ray spectroscopy), surface roughness and topography (atomic force microscopy) were evaluated at the 14-day period. Data were analyzed statistically by two-way ANOVA and Tukey's test (α=0.05). Significant microhardness reduction was observed at the 7 th and 14 th days for 10% CP gel, and for all bleaching times for 16% CP gel (p<0.05). At the 14-day period, a significant decrease in Ca and P content, increase on surface roughness (p<0.05) as well as on picks and valleys distance were observed when both bleaching gels were used. These enamel alterations were more intense for 16% CP gel. It was concluded that both CP-based gels promoted loss of mineral structure from enamel, resulting in a rough and porous surface. However, 16% CP gel caused the most intense adverse effects on enamel.

O objetivo do presente estudo foi comparar o efeito de um gel com 16% de peróxido de carbamida (PC) sobre a estrutura mineral e morfologia do esmalte dental com os efeitos de um gel com 10% de PC. Blocos de esmalte provenientes de incisivos bovinos foram submetidos a 14 dias de tratamento (8 h/dia) com géis com 10 ou 16% de PC. A microdureza Knoop foi avaliada antes do clareamento e 1, 7 e 14 dias pós-tratamento (50 g/15 s). O conteúdo mineral (EDX), rugosidade de superfície e topografia (MFA) foram avaliados no período de 14 dias (ANOVA a dois critérios e teste de Tukey; α=0,05). Redução significante na microdureza foi observada nos períodos de 7 e 14 dias para o gel com 10% de PC, e em todos os períodos para o gel com 16% de PC (p<0,05). No período de 14 dias, uma diminuição significante no conteúdo de Ca e P, aumento na rugosidade de superfície (p<0,05), bem como na distância entre picos e vales foram observados para ambos os agentes clareadores usados. Estas alterações foram mais intensas para o gel com 16% de PC. Pôde-se concluir que ambos os géis à base de PC promoveram perda de estrutura mineral do esmalte, resultando em superfície mais rugosa e porosa. Porém, o gel com 16% de PC causou efeitos adversos mais intensos no esmalte dental.
Keywords: atomic force microscopy; carbamide peroxide; tooth enamel; hardness tests; tooth bleaching